Cartas de nuevas y avisos manuscritos en la época de la imprenta. Su difusión de noticias sobre América durante el siglo XVI - Pieper, Renate (Cuadernos de Historia Moderna, 2006)
As the printing press spread from northem to southem Europe, anonymous manuscript gacettes diffused in opposite direction from Italy to Flanders. Combining traditional techniques of copying and exchanging manuscripts with a professional system of copyists and translators the gacettes developed to a rapid and precise means of communication during the 16th century. At first its centers were located at Venice and Rome, in the second hal fof the century Antwerp and Cologne joined in.